Western Himalaya and Tibet : A Narrative of a Journey Through the Mountains of Northern India During the Years 1847-8 - Thomson, Thomas, 1817-1878 (Salt Lake City, UT : Project Gutenberg, 2013)
"Western Himalaya and Tibet" by Thomas Thomson is a narrative account of a journey through the mountainous regions of Northern India written in the mid-19th century. This expedition aimed to explore the geography, flora, and climate of the Western Himalayas and Tibet, reflecting scientific interests of the time. The book is a detailed study of the author's travels, observations, and experiences in these less-explored terrains. The opening of the narrative introduces the author, Dr. Thomas Thomson, as he receives his assignment to join a mission to Tibet from the Governor-General of India in May 1847. Thomson outlines his journey from Firozpur to Simla, describing the gradual transition from low, flat plains to the stunning Himalayan elevations. He vividly depicts the striking aspects of the landscape, the changing vegetation, and the complexities of recognizing mountain ranges while approaching them. The narrative sets a tone of adventure and exploration, highlighting the meticulous observations and empirical approach that characterize this scientific expedition. (This is an automatically generated summary.)
Release date is 2013-02-20
E-text prepared by Melissa McDaniel and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Tibet Autonomous Region (China) -- Description and travel; Thomson, Thomas, 1817-1878 -- Travel -- Himalaya Mountains Region; Thomson, Thomas, 1817-1878 -- Travel -- China -- Tibet Autonomous Region; Himalaya Mountains Region -- Description and travel